2015
DOI: 10.1089/gtmb.2015.0132
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA Copy Number in Egyptian Patients with Hepatitis C Virus-Related Hepatocellular Carcinoma

Abstract: mtDNA content analysis could serve as a noninvasive molecular biomarker that reflects tumor burden in HCV-HCC cases and could be used as a predictor of HCC risk in patients of HCV-cirrhosis. In addition, the nonsignificant difference of mtDNA level between HCV-cirrhosis patients and healthy controls could eliminate the gray zone created by the use of alpha-fetoprotein in some cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…Our analysis included 36 studies that focused on diverse cancer types from different origins around the world 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 . To reduce the uncertainty induced by confusing factors in the meta-analysis, we evaluated the association between mtDNA content with cancer risk in an overall analysis, as well as stratified analyses by cancer types, genders, ages, ethnicity and life styles.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis included 36 studies that focused on diverse cancer types from different origins around the world 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 . To reduce the uncertainty induced by confusing factors in the meta-analysis, we evaluated the association between mtDNA content with cancer risk in an overall analysis, as well as stratified analyses by cancer types, genders, ages, ethnicity and life styles.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we for the first time identified leukocyte mtDNA content as an independent prognostic factor for HCC, indicating that high leukocyte mtDNA content was associated with poor OS and RFS of patients. In comparison, Hashad et al have reported that HCV-related HCC patients with multicentric hepatic lesions have significantly lower mtDNA content than those with less advanced disease, suggesting that functional roles of mtDNA copy number may be disease-specific [16]. Collectively, these findings support the point of view that mtDNA content variations are involved in the progression of cancer, although the molecular mechanisms underlying the regulation of mtDNA copy number, especially in lymphocytes from cancer patients, remains to be largely unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Yamada et al have found that HCC tissues have a reduced copy number of mtDNA when compared with paired non-tumor tissues, which is associated with malignant potential of HCC [15]. In recent years, there are a series of reports on the association of the mtDNA content in peripheral blood lymphocytes (PBLs) with cancer susceptibility [1620]. However, only two studies have indicated that mtDNA content in PBLs is associated with breast cancer progression and CRC prognosis [21, 22].…”
Section: Introductionmentioning
confidence: 99%
“…A study suggested that mtDNA content analysis from peripheral blood could serve as a noninvasive biomarker and predictor for hepatocellular carcinoma risk in patients with hepatitis C [152]. Supported by other authors, their study used plasma and found it as a promising complementary sample alongside tissue specimens that served as a predictor for diagnosis and prognosis of lung cancer [154].…”
Section: Circulatingmentioning
confidence: 98%
“…Naturally alike, vigorous researches were conducted to find the potential link between cf-mtDNA and various cancers. cf-mtDNA is much more preferable as a noninvasive biomarker with easier sampling procedures and handling during molecular analysis [19,102,108,135,136,140,152,153].…”
Section: Circulatingmentioning
confidence: 99%